Public Interest Litigation in Nigeria and Locus Standi Debacle in Edun V. Governor of Delta State: Lessons From India, United Kingdom and South Africa - Eyongndi, David Tarh-Akong; Onu, Kingsley Osinachi Nnana; Okwori, Moses Arome (Lentera Hukum, 2024)
This paper reviews Nigeria’s Court of Appeal decision in Edun v. Governor of Delta State where the court held that the appellant lacks locus standi to challenge the validity of the Pension Rights of the Governor and Deputy Governor of Delta State Law, 2008 because he has neither suffered injury nor shown sufficient interest over and above that of every Deltan. It uses legal functionalism theory through analytical methodology while relying on primary and secondary data in examining the development of locus standi in Nigeria and the impact of its restrictive application on justice delivery. Considering the need to respond to contemporary developments and further the course of justice, it argues for the liberalization of locus standi by Nigerian courts drawing from the practice in India, the United Kingdom, and South Africa. It argues that the liberalization of locus standi will encourage public interest litigation hence, the orthodox requirements of having “sufficient interest” and “suffering/likely to suffer injury” indicia have become otiose to justice and should lead to the discountenancing of the restrictive application. It examines the effect of the judgment on PIL and whether the decision of the Nigerian Supreme Court (NSC) in Centre for Pollution Watch v. NNPC and the Fundamental Rights (Enforcement Procedure) Rules 2009 could be a useful harbinger for liberalization of locus standi. It recommends an appeal of Edun’s Case to the Supreme Court and the upturning of the same as leeway to liberalizing locus standi in favor of public interest litigation.KEYWORDS: Common law, Justice, Locus standi, Litigant, Injury, Nigeria.